The TEKNOLOGI OLAHAN MAKANAN BERBASIS JAMUR DALAM RANGKA MENGEMBANGKAN HOME INDUSTRY AGROBISNIS DI DESA LINGSUH, KECAMATAN RAJA BASA, BANDAR LAMPUNG - Utami, Herti (Lembaga Penelitian dan Pengabdian Universitas Lampung, 2019)
Mushroom cultivation especially a kind of paddy straw mushroom and oyster mushroom done by the farmers in Lingsuh, Raja Basa, Bandar Lampung. In post harvest handling of crops one of obstacles is fast rot the mushrooms if the production were abundant. This activity Program Kemitraan Masyarakat (PKM) provide an alternative handling after harvest mushrooms to be a processed products mushroom economy value higher and acceptable consumers, if comparared by selling fresh mushrooms. By processing mushrooms to be food products will provide alternatives to consumer of a new mushrooms based product. This product have a long storage time and open opportunities to develop home industry agribusiness based in this process mushrooms. A common purpose of PKM is empower potentials by farmers groups mushrooms in Lingsuh. Food products that would be produced are crackers and crispy mushrooms. The method of PKM activity involved the partners (the farmers) in the overall of activities. The outer of this main activity are crackers and crispy mushrooms, crisp and tasteful with various variant of this products. From this activity, giving production equipment would be very helpful for both of the groups farmer in doing production process. In this activity was expected to increase the income economically through food products based mushrooms.